Penerapan Model Project Based Learning (PJBL) Pada Mata Pelajaran Tematik Kelas III Di Madrasah Ibtidaiyah Negeri 1 Banyuwangi Tahun Pelajaran 2021/2022 - Damayanti, Renita Fitria; indrianto, Nino (Pendidikan Islam Pascasarjana IAIN Jember, 2022)
MIN 1 Banyuwangi is a school located in Banyuwangi city and has implemented a project-based learning model in the classroom; the results of observations show that there are students who are less active because they are not involved in learning in the school. Therefore, applying the project-based learning model aims to engage students more in learning. This research has a focus such as: 1) How to implement the Project Based Learning (PjBL) Model in Class III Thematic Subjects at Madrasah Ibtidaiyah Negeri 1 Banyuwangi in the 2021/2022 academic year; 2) How is the Evaluation in the Project Based Learning (PjBL) Model in Class III Thematic Subjects at Madrasah Ibtidaiyah Negeri 1 Banyuwangi for the 2021/2022 Academic Year. Meanwhile, the goal is to determine the Implementation and Evaluation of the Project Based Learning (PjBL) model in Class III thematic subjects at Madrasah Ibtidaiyah Negeri 1 Banyuwangi in the 2021/2022 academic year. This approach uses qualitative and uses case-study research. This study's subjects include principals, third-grade students, and third-grade guardians. The collection consists of observation, interviews, and documentation. The data analysis technique is an interactive model from Miles, Huberman, and Saldana. The results of the research on the application of the project based learning model show that: 1) The implementation of the project based learning model has several stages, namely learning planning which includes teachers making lesson plans and syllabus in schools with other teachers, with the aim that the learning process runs optimally, then on implementation There are also three learning activities, namely preliminary activities in the form of teachers providing motivation, teachers checking student attendance, and others, the two core activities include (determining questions, designing plans, making schedules, monitoring students, testing results, and evaluating experiences), c) and lastly, the closing activity here is where the teacher reflects and provides reinforcement so as not to forget the material that has been given, as well as providing motivation and collecting the work then praying together before going home; 2) Evaluation of the project based learning model, namely an attitude assessment in the form of spiritual and social, the second is an assessment of knowledge in the form of written and non-written tests, the last is an assessment of skills in the form of the initial process of making a project until the end of making a project.